EFEKTIVITAS MODEL PEMBELAJARAN GRUP INVESTIGASI TERHADAP KEMAMPUAN PENALARAN MATEMATIS MAHASISWA PADA MATERI RUANG VEKTOR - Cita Dwi Rosita (AlphaMath : Journal of Mathematics Education, 2015)
The aim of the study are, to analyze the effectiveness of IG Linear Algebra Learning in which is indicated by a. completion mathematic reasoning; b. a positive effect of activities to the mathematic reasoning; and c. the mathematic reasoning skill of experiment class is better than expository class. The results are Investigation Group based learning is effective as shown in point a. The mathematic reasoning skill is completed classically in which it reaches 71.69 upper than 65 normal point and reaches upper than 75 % individual; b. Motivation and activities of the students provide positive influence the mathematic reasoning for 91.7 % contribution altogether; c. Mathematic reasoning of experimental class is 71.96 better than the average score of 64.42 expository class. Keywords: Investigation Group, mathematical reasoning